Robert Ludlum's The Treadstone resurrection - Hood, Joshua (G.P. Putnam's Sons, 2020)
"The first novel in an explosive new series inspired by Robert Ludlum's Bourne universe, The Treadstone Resurrection introduces an unforgettable hero and the shadowy world that forged him.."--